A case of PRES following intracranial hypotension, with spontaneous resolution with epidural blood patch - Mamilla, Sarada Murali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Posterior reversible encephalopathy syndrome (PRES (also known as reversible posterior leukoencephalopathy syndrome)) presents with rapid onset of symptoms including headache, seizures, altered consciousness, and visual disturbance. It is often but by no means always associated with acute hypertension. Diffusion-weighted MRI is the most sensitive exam to confirm the diagnosis of PRES. If promptly recognized and treated, the clinical syndrome usually resolves within a week, and the changes seen in magnetic resonance imaging (MRI) resolve over days to weeks. Posterior reversible encephalopathy syndrome is an increasingly recognized disorder, with a wide clinical spectrum of both symptoms and triggers, and yet it remains poorly understood. Differential diagnosis includes venous sinus thrombosis, cerebral haemorrhage, encephalitis, vasculititis and metabolic encephalopathys. No clinical trials have evaluated the management of PRES, but rapid withdrawal of the trigger appears to hasten recovery and to avoid complications: for example, aggressive blood pressure management, withdrawal of the offending drug, or delivery in eclampsia. We report a case of women presenting with severe headache, tonic clonic convulsions 7 days after spinal anaesthesia for caesarean delivery, MRI showed evidence of intracranial hypotension and posterior reversible encephalopathy syndrome. She was treated with Blood patch which lead to complete resolution of symptoms and radiological findings. The possible pathogenetic relationship between intracranial hypotension, secondary to the inadvertent dural puncture, and PRES is discussed. Prompt diagnosis and proper treatment results in complete cure without permanent neurological sequelae.